Visions of France. Provence [videorecording (DVD)] - Hammond, Roy A. (Acorn Media, 2005)
Inhabited since prehistoric times, Provence is bounded by the Alps to the east and the Rhone River to the west. Its timeless charms, celebrated by writers and painters over the centuries, have been more dazzling than in this aerial tour, enhanced by a historical narrative and set to regional music.